Optimizing beam models for dosimetric accuracy over a wide range of treatments. (February 2019) - Chen, Josephine; Morin, Olivier; Weethee, Brandon; Perez-Andujar, Angelica; Phillips, Justin; Held, Mareike; Kearney, Vasant; Han, Dae Yup; Cheung, Joey; Chuang, Cynthia; Valdes, Gilmer; Sudhyadhom, Atchar; et al.
Highlights: A systematic procedure for optimizing photon beam model parameters is demonstrated. A variety of non-standard beam measurements is used to adjust model parameters. Dosimetric errors as high as 10% were discovered as part of the process. The final dosimetric accuracy was generally within 3%. Abstract: This work presents a systematic approach for testing a dose calculation algorithm over a variety of conditions designed to span the possible range of clinical treatment plans. Using this method, a TrueBeam STx machine with high definition multi-leaf collimators (MLCs) was commissioned in the RayStation treatment planning system (TPS). The initial model parameters values were determined by comparing TPS calculations with standard measured depth dose and profile curves. The MLC leaf offset calibration was determined by comparing measured and calculated field edges utilizing a wide range of MLC retracted and over-travel positions. The radial fluence was adjusted using profiles through both the center and corners of the largest field size, and through measurements of small fields that were located at highly off-axis positions. The flattening filter source was adjusted to improve the TPS agreement for the output of MLC-defined fields with much larger jaw openings. The MLC leaf transmission and leaf end parameters were adjusted to optimize the TPS agreement for highly modulated intensity-modulated radiotherapy (IMRT) plans. The final model was validated for simple open fields, multiple field configurations, the TG 119 C-shape target test, and a battery of clinical IMRT and volumetric-modulated arc therapy (VMAT) plans. The commissioning process detected potential dosimetric errors of over 10% and resulted in a final model that provided in general 3% dosimetric accuracy. This study demonstrates the importance of using a variety of conditions to adjust a beam model and provides an effective framework for achieving high dosimetric accuracy.